Impact of Moderate to Severe Renal Impairment on Mortality and Appropriate Shocks in Patients with Implantable Cardioverter Defibrillators - Venkata M. Alla; Kishlay Anand; Mandeep Hundal; Aimin Chen; Showri Karnam; Tom Hee; Claire Hunter; Aryan N. Mooss; Dennis Esterbrooks; Syed M. Mohiuddin (Cardiology Research and Practice)
Background. Due to underrepresentation of patients with chronic kidney disease (CKD) in large Implantable-Cardioverter Defibrillator (ICD) clinical trials, the impact of ICD remains uncertain in this population. Methods. Consecutive patients who received ICD at Creighton university medical center between years 2000–2004 were included in a retrospective cohort after excluding those on maintenance dialysis. Based on baseline Glomerular filtration rate (GFR), patients were classified as severe CKD: GFR < 30 mL/min; moderate CKD: GFR: 30–59 mL/min; and mild or no CKD: GFR ≥ 60 mL/min. The impact of GFR on appropriate shocks and survival was assessed using Kaplan-Meier method and Generalized Linear Models (GLM) with log-link function. Results. There were 509 patients with a mean follow-up of 3.0 + 1.3 years. Mortality risk was inversely proportional to the estimated GFR: 2 fold higher risk with GFR between 30–59 mL/min and 5 fold higher risk with GFR < 30 mL/min. One hundred and seventy-seven patients received appropriate shock(s); appropriate shock-free survival was lower in patients with severe CKD (GFR < 30) compared to mild or no CKD group (2.8 versus 4.2 yrs). Conclusion. Even moderate renal dysfunction increases all cause mortality in CKD patients with ICD. Severe but not moderate CKD is an independent predictor for time to first appropriate shock.